ID1/ID3 mediate the contribution of skin fibroblasts to local nerve regeneration through Itga6 in wound repair. (14th September 2021) - Chen, Zelin; Shen, Gufang; Tan, Xu; Qu, Langfan; Zhang, Can; Ma, Le; Luo, Peng; Cao, Xiaohui; Yang, Fan; Liu, Yunsheng; Wang, Yu; Shi, Chunmeng
Abstract: Cutaneous wound healing requires intricate synchronization of several key processes. Among them, local nerve regeneration is known to be vitally important for proper repair. However, the underlying mechanisms of local nerve regeneration are still unclear. Fibroblasts are one of the key cell types within the skin whose role in local nerve regeneration has not been extensively studied. In our study, we found skin fibroblasts were in tight contact with regenerated nerves during wound healing, while rare interactions were shown under normal circumstances. Moreover, skin fibroblasts surrounding the nerves were shown to be activated and reprogrammed to exhibit neural cell‐like properties by upregulated expressing inhibitor of DNA binding 1 (ID1) and ID3. Furthermore, we identified the regulation of integrin α6 (Itga6) by ID1/ID3 in fibroblasts as the mechanism for axon guidance. Accordingly, transplantation of the ID1/ID3‐overexpressing fibroblasts or topical injection of ID1/ID3 lentivirus significantly promoted local nerve regeneration and wound healing following skin excision or sciatic nerve injury. Therefore, we demonstrated a new role for skin fibroblasts in nerve regeneration following local injury by directly contacting and guiding axon regrowth, which might hold therapeutic potential in peripheral nerve disorders and peripheral neuropathies in relatively chronic refractory wounds. Abstract : Skin fibroblasts contribute to local nerve regeneration by directly guiding axon regrowth, which suggests a potential therapeutic strategy for peripheral nerve disorders and relatively chronic refractory wounds.